Comparison of effectiveness of Salvadora Persica whitening toothpaste with commercial whitening toothpaste at removing stain - Mahanani, Erlina Sih; Arief, Erry Mochamad; Samuel, Samantha Victoria (Padjadjaran Journal of Dentistry, 2009)
The miswak, a traditional chewing stick for cleaning teeth, is made from the plant Salvadora persica. It contains a wide range of healthy components in maintaining good oral hygiene. The objective of this study is to determine the effectiveness of whitening toothpaste containing Salvadora persica extract at removing tea and chlorhexidine stain by comparing with one of commercially available whitening toothpaste and drinking water as a control group. A randomized experimental study was done. The standard method cycled clear acrylic specimens through artificial saliva, 0.2% chlorhexidine and tea on the hour 8 times per day and stain were measured using a spectrophotometer to achieve baseline reading. Test interventions were 2 whitening kinds of toothpaste; whitening toothpaste containing Salvadora persica extract (group A), commercial whitening toothpaste (group B) and drinking water as a control group (group C). Treatment interventions were done at 09:00 and 16:00 by exposing the specimens to slurries of each treatment for 2 minutes. The specimens remained in the artificial saliva between each cycles day and night. At the end of the day, the stain was assessed by spectrophotometer and Lobene Stain Index. The comparison of total stain removal assessed by spectrophotometer on day 5 between all groups was significant (p=0.007). The median of total stain removal and visual assessment recording using Lobene stain index showed Salvadora persica whitening toothpaste scored more reduction of staining followed by commercial whitening toothpaste and then control group. As a conclusion, the whitening toothpaste containing Salvadora persica is more effective at removing tea and chlorhexidine stain.